The First 2 Years of Activity of a Specialized Organ Procurement Center: Report of an Innovative Approach to Improve Organ Donation. Issue 6 (7th January 2017) - Marsolais, P.; Durand, P.; Charbonney, E.; Serri, K.; Lagacé, A.‐M.; Bernard, F.; Albert, M.
Abstract : The number of patients requiring organ transplants continues to outgrow the number of organs donated each year. In an attempt to improve the organ donation process and increase the number of organs available, we created a specialized multidisciplinary team within a specialized organ procurement center (OPC) with dedicated intensive care unit (ICU) beds and operating rooms. The OPC was staffed with ICU nurses, operating room nurses, organ donor management ICU physicians, and multidisciplinary staff. All organ donors within a designated geographic area were transferred to and managed within the OPC. During the first 2 years of operation, 126 patients were referred to the OPC. The OPC was in use for a total of 3527 h and involved 253 health workers. We retrieved 173 kidneys, 95 lungs, 68 livers, 37 hearts, and 13 pancreases for a total of 386 organs offered for transplantation. This translates to a total of 124.6 persons transplanted per million population, which compares most favorably to recently published numbers in developed countries. The OPC clearly demonstrates potential to increase the number of deceased donor organs available for transplant. Further studies are warranted to better understand the exact influence of the different components of the OPC on organ procurement. Abstract : The authors describe the results of the first two years of operation of a specialized organ procurement center as an effective strategy to improve organ donation, demonstrating significant improvement in the overall organ donation process and increasing organ availability for transplant.